Drug Related Esophagitis - René Beaudry; Franco Colizza (Canadian Journal of Gastroenterology)
Esophageal injury after ingestion of various drugs often goes unrecognized. Two cases of tetracycline induced esophagitis are reported. The main presenting symptoms were odynophagia and dysphagia for both solids and liquids following the first two or three doses. Esophageal endoscopy revealed the presence of acute esophageal ulcers in both cases. Symptomatic relief was achieved by discontinuation of the drug and the use of viscous lidocaine and antacids. Recovery was complete within a few days. Recognition of this entity will help in its diagnosis and treatment, and should prevent further complications.